Metabolomic analysis of umami taste variation in Pyropia haitanensis throughout the harvest cycle - Zihan Yuan; Haibin Pan; Juanjuan Chen; Yuting Zhang; Qijun Luo; Rui Yang; Peng Zhang; Tiegan Wang; Haimin Chen (Food Chemistry, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Mn vacancy engineering design of Fe/Mn based cathodes for breaking the spell between “sodium limiting” in air-stabilization and “sodium promoting” on kinetics - Rui Huang; Shaohua Luo; Qi Sun; Xin Yan; Haoran Zhang; Lixiong Qian; Xin Liu; Xingzhong Cao; Peng Zhang; Shengxue Yan (Chemical Engineering Journal, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Prolonged exposure to NaAsO2 induces thyroid dysfunction and inflammatory injury in Sprague‒Dawley rats, involvement of NLRP3 inflammasome‒mediated pyroptosis - Lili Fan; Qian Song; Ying Jin; Rui He; Heng Diao; Peng Luo; Dapeng Wang (Archives of Toxicology, 2024)

Applications of electrospun nanofibers in food safety and quality analysis: A review - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Lin Luo; Zhen-Lin Xu (Trends in Food Science & Technology, 2024)

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Micafungin protects mouse heart against doxorubicin-induced oxidative injury via suppressing MALT1-dependent k48-linked ubiquitination of Nrf2 - Li-Qun Lu; Ming-Rui Li; Lin-Lu Huang; Yan-Xi Che; Ya-Nan Qi; Xiu-Ju Luo; Jun Peng (Chemico-Biological Interactions, 2024)

Effects of air frying on protein digestive properties in scallop (Patinopecten yessoensis) adductor muscles and the mechanisms involved - Zi-Ye Wang; Ying Luo; Rui Zheng; Shuo Lv; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Bioscience, 2024)

Covalent organic framework with bioinspired N,S-anchored single atom sites for photocatalytic CO2 reduction reaction - Zi-Xian Pan; Shuai Yang; Xi Chen; Jing-Xian Luo; Rui-Zhi Zhang; Peng Yang; Qing Xu; Jie-Yu Yue (Chemical Engineering Journal, 2024)

The role of hormones in the regulation of lactogenic immunity in porcine and bovine species - Kexin Hua; Dan Liu; Qianshuai Xu; Yuna Peng; Yu Sun; Rongrong He; Rui Luo; Hui Jin (Domestic Animal Endocrinology, 2024)

Boosting peroxymonosulfate activation over partial Zn-substituted Co3O4 for florfenicol degradation: Insights into catalytic performance, degradation mechanism and routes - Xinyang Wang; Xinyu Luo; Rui Li; Yu Chang; Jianbiao Peng; Weilai Wang; Haijin Liu; Guangxuan Yan; Pengkun Wei; Zhiguo Cao (Chemical Engineering Journal, 2024)

Rapid immobilization of arsenic in contaminated soils by microwave irradiation combined with magnetic biochar: Microwave-induced electron transfer for oxidation and immobilization of arsenic (III) - Dengcai Zhang; Junhao Lin; Juan Luo; Shichang Sun; Xi Zhang; Rui Ma; Juan Peng; Fei Ji; Shuaifei Zheng; Zhen Tian; Ning Ma (Science of The Total Environment, 2024)

TRPML1 contributes to antimony-induced nephrotoxicity by initiating ferroptosis via chaperone-mediated autophagy - Lei Liu; Chao Luo; Dongnan Zheng; Xuehai Wang; Rui Wang; Wenjie Ding; Zhaoping Shen; Peng Xue; Shali Yu; Yifei Liu; Xinyuan Zhao (Food and Chemical Toxicology, 2024)